2019
DOI: 10.1080/19476337.2018.1547793
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical stability of bread fortified with tilapia-waste flour

Abstract: The physicochemical stability of six bread formulations with different tilapia flour (BTF) levels (0%, 2.5%, 5%, 10%, 15%, and 20%) in substitution to wheat flour was investigated regarding moisture content, water activity (a w ), pH, instrumental color parameters, texture profile, lipid and protein oxidation on days 0, 2, 4, 6 and 8 at 25°C. BTF10%, BTF15%, and BTF20% displayed lower (P < 0.05) moisture, aw, lightness index, cohesiveness, springiness and resilience, and higher (P < 0.05) pH, redness index, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Bread fortification is a common practice used to prevent malnutrition and nutritional deficiencies in populations and adding functional properties, but additional ingredients can also influence other parameters, such as appearance, flavor and taste [15,16] Presence of various ingredients in bread, such as plants' components and extracts, can also influence the physicochemical stability and quality parameters during storage [17,18]. In studies in which bread was enriched with Garcinia mangostana fruit extract, it was shown that such an addition increases the attractiveness of the bread in terms of its functionality, while reducing the bread volume [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bread fortification is a common practice used to prevent malnutrition and nutritional deficiencies in populations and adding functional properties, but additional ingredients can also influence other parameters, such as appearance, flavor and taste [15,16] Presence of various ingredients in bread, such as plants' components and extracts, can also influence the physicochemical stability and quality parameters during storage [17,18]. In studies in which bread was enriched with Garcinia mangostana fruit extract, it was shown that such an addition increases the attractiveness of the bread in terms of its functionality, while reducing the bread volume [19].…”
Section: Introductionmentioning
confidence: 99%
“…As the storage time increased, water activity decreased. This could be due to protein denaturation, which causes more electrostatic connections between proteins and polysaccharides, resulting in water entrapment, intermolecular network, and decreased free water content, all of which are linked to lower moisture content and aw in foods (Monteiro et al, 2019). In general, amylopectin retrogradation is the most common process for bread staling.…”
Section: Resultsmentioning
confidence: 99%
“…During storage, packaged food is exposed to gases (Nitrogen, oxygen, carbondioxide and others) as well as ambient circumstances (temperature, humidity) that can affect the shelf life of the food. As a result, the rate of gas diffusion through the packaging film may be a limiting factor in reaching appropriate shelf life (Monteiro et al, 2019). Packaging materials serve as a barrier between the food and the surrounding by limiting the transfer of light, heat, moisture, and gases, as well as bacteria and insects (Deng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate content was estimated as the difference between 100% and the sum of the moisture, protein, ash, and lipid contents. Energy value was calculated as energy value (kcal/100 g) = 4 × protein% +9 × lipid% + 4 × carbohydrate% [15].…”
Section: Preparation Of Snack Bars (Sbs)mentioning
confidence: 99%